Pet abandonment attitudes in Portugal: correlates to responsibility and justification - Jacobetty, R.; Lopes, D.; Rodrigues, D. L. (Canine Science Forum, 2018)
Introduction: People abandon pets for multiple reasons, but several studies reported human-related factors (not animal-related) to be the most common. An approach based on social psychological related variables is a useful framework to tackle the pet abandonment issue. While there is extant research on pet abandonment predictors and outcomes, there is a notable lack of research on pet abandonment attitudes. Hypothesis: This study analysed attitudes towards pet abandonment in a Portuguese sample, and whether sociodemographic characteristics, expectations, behaviours and personality traits correlate to these attitudes. Method: A cross-sectional study was conducted via an online survey. The sample consisted of 589 Portuguese participants that have or previously had a dog or cat. The diversity of the survey’s questions helped find variables associated with attitudes towards pet abandonment. Hierarchical regression analyses were carried out. Results: An exploratory factorial analysis revealed two dimensions to the Pet Abandonment Attitude Scale (PAAS): pet abandonment as an irresponsible behaviour (PA-IRR) and pet abandonment as a justifiable behaviour (PA-JUST). These dimensions were tested as outcomes of other variables, such as individual sociodemographics (e.g., age, sex, income, children), personal history with pets (e.g., pet caretaker, works with animals), expectations and intentions towards pets (e.g., viewing pets as a burden, reasons to have a pet), and intra-individual characteristics (e.g., personality traits, trust in animals). PA-IRR attitude was found to be correlated to younger participants, that do not view pets as a burden, have a high agreeableness personality trait and a high trust in animals (all p’s < .05). PA-JUST attitude was found to be correlated to participants with children, that do not work with animals, that view animals as a burden, have a low conscientiousness personality trait and low trust in animals (all p’s < .05). Discussion: The responsibility and justification dimensions found in the PAAS suggest two important psychological constructs in the Portuguese attitudes towards pet abandonment. To find people viewing abandonment as irresponsible was not surprising. To discover that abandonment can be viewed as justifiable in certain circumstances is a powerful tool to develop the research. These constructs and profiles can be useful in the development of adoption triage systems to signal human-related risk for abandonment.